Pendampingan Perhitungan Tarif Air Bersih SPAMdes Ngudi Tirto Kulon Progo: Assistance in Calculation of Clean Water Rates for SPAMdes Ngudi Tirto Kulon Progo - Barid, Burhan; Rizani, Aisyah Azzahra; Ikhsan, Jazaul; Lesmana, Surya Budi; Hairani, Ani; Widodo, Wahyu; Robial, Siti Muawanah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Clean water management in rural areas has not provided optimal results. The applied water tariffs are not enough to cover the required production and operational costs. The existing prices are still based on agreements with the community, who tend to want the lowest rates. Reasonable pricing needs to be re-evaluated so that all production and operational costs can be covered, and there is a reserve budget for development. This community service activity involves assistance in calculating clean water tariffs with the managers of the Independent Water Management Organization for the Rural Clean Water Supply System (OKAM SPAMDes) Ngudi Tirto in Kebonromo Hamlet, Giripurwo Village, Girimulyo District, Kulon Progo Regency. Assistance begins with the collection of financial data, which includes income and expenditure budgets. The determination of water tariffs based on these data refers to Permendagri Number 21 of 2020. The data used for analysis are financial reports and water usage by SPAMDES Ngudi Tirto customers in 2023. The calculation results will be presented at the next meeting through routine group meetings. The minimum reasonable basic clean water tariff price is IDR. 6,500/m³, which was previously only Rp. 5,000/m³. OKAM Ngudi Tirto now understands the calculation of the water tariff to cover operational costs and obtain profit from the SPAMDes.